2015
DOI: 10.1039/c5ta00506j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the CO2 separation performance of composite membranes by the incorporation of amino acid-functionalized graphene oxide

Abstract: Amino acid-functionalized graphene oxide nanosheet-incorporated composite membranes significantly enhanced the CO2/CH4(N2) diffusivity, reactivity and solubility selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 160 publications
(96 citation statements)
references
References 61 publications
3
93
0
Order By: Relevance
“…The membranes doped with NaH 2 PO 4 , Na 2 HPO 4 and Na 3 PO 4 showed the stretching vibration peaks of P@O at 1415, 1402, and 1437 cm 21 , these characteristic bands suggested that the phosphate salts were successfully introduced into the polymer matrix. All membranes showed the representative peaks of -OH at the position of 3445 cm 21 , phosphate salts were presented in SPEEK membranes, the corresponding peak intensity increased, which indicating the enhance hydrophilic of membranes.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The membranes doped with NaH 2 PO 4 , Na 2 HPO 4 and Na 3 PO 4 showed the stretching vibration peaks of P@O at 1415, 1402, and 1437 cm 21 , these characteristic bands suggested that the phosphate salts were successfully introduced into the polymer matrix. All membranes showed the representative peaks of -OH at the position of 3445 cm 21 , phosphate salts were presented in SPEEK membranes, the corresponding peak intensity increased, which indicating the enhance hydrophilic of membranes.…”
Section: Resultsmentioning
confidence: 92%
“…) is higher than that of sulfonic acid with water molecule (44.4 KJ mol 21 ), 27 which indicated that phosphonic acid has easier capacity to bind with water molecule and retained more water. Furthermore, phosphate salts has different acid-base properties, the acid2base interaction between salts and CO 2 could increase the solubility of CO 2 .…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Mixed matrix membranes (MMMs) composed of an inorganic filler and a polymer matrix have exhibited the potential of surpassing the trade-off limit [1,[4][5][6][7][8][9][10][11][12]. Fillers such as porous zeolite [13,14], silica nanoparticles [15,16], carbon nanotubes (CNTs) [9,17,18] metal-organic frameworks [19][20][21][22][23], and graphene oxide [24,25] have been doped in different polymer matrix to develop new MMMs with improved gas separation performance.…”
Section: Introductionmentioning
confidence: 99%